PERBANDINGAN KETAHANAN PENYAKIT BULAI JENIS (Peronosclerospora Philippinensis dan Peronosclerospora Maydis) CALON VARIETAS JAGUNG HIBRIDA - Suntoko suntoko; Chitra Dewi Yulia Christie; Febri Hendrayana; Nia Agus Lestari (Jurnal Agriovet, 2024)
This study aims to compare the resistance of hybrid maize varieties from "PT Cipta Makmur Pertiwi" to downy mildew caused by P. philippinensis and P. maydis species. This research was conducted from May to August 2020 at IP2TP Balitsereal Bontobili, Gowa, South Sulawesi and in July-October 2020 in Kencong Village, Kepung District, Kediri Regency. The experiment was arranged in a group design with 3 replications. Each line, spacing of 70 x 20 cm, population of 120-150 plants. For comparison, the susceptible variety was the Anoman variety and the resistant variety Pertiwi 6. The susceptible and resistant varieties were planted side by side in every 3 lines and varieties tested. The results showed that strain TB 06 (13.60%) was classified as resistant and strain TB04 (35.89%), ADV 777 (26.38%) and ADTR 5123 27.24% was classified as moderately resistant to downy mildew caused by Peronosclerospora species. . Test line TB 06 infected 19.59%, or classified as resistant, in a susceptible comparison (Anoman) the intensity reached 99.30% (very susceptible) and was positively corrected in a resistant comparison (Pertiwi 6) infected 14.58 or resistant to disease downy mildew caused by the species Peronosclerospora maydis. From the results of the study, for the ADTR5123 variety in the Bontobili region, resistance to downy mildew 12.47% to 27.24% was classified as moderately resistant. While the ADTR5123 variety in the Kediri region was resistant to downy mildew from 92.51% to 94.24% classified as very susceptible